(untitled) (Acta Scientiarum. Health Sciences, 2015)
The present study aimed to investigate the interaction between the blood cells, inflammatory markers, oxidative stress parameters and delayed onset muscle soreness (DOMS) after a session of resistance exercise (SRE). The sample consisted of sixteen untrained men (26.4±5 years; 25.9±3 kg m-2). The SRE was composed of 4 sets of 10 repetitions maximum (extensor bench, squat and leg press) for each exercise. Complete blood cell count, C-reactive protein (CRP), creatine kinase (CK), lipid peroxidation and antioxidant capacity against peroxyl radicals were previously evaluated (baseline), and at 0, 30 and 120 min. after the SRE. DOMS was assessed 24 hours after the exercises. Immediately after the SRE, an increase of blood cell number was observed; returning to baseline after 30 min. However, after 120 min., neutrophils showed higher values than the baseline and 30 min. assessments. CK and CRP increased progressively throughout the experiment. LPO increased immediately and 120 min. after the SRE. Untrained volunteers presented an apparent biphasic inflammatory response after an acute SRE and the changes in oxidative stress, inflammatory markers and leukocytosis were best evidenced two hours after exercise.